Pengaruh Karya Yusuf Al-Qardhawi Dalam Pendidikan Agama Islam Pada Era Digital - Azzra Pernanda; Syahrul Holid (Journal on Education, 2024)
The works of Yusuf al-Qaradawi have had a significant impact on the development of Islamic religious education, particularly in the current digital era. His writings encompass various aspects of modern life and offer relevant Islamic insights that can be applied in diverse contexts, including education. In an age characterized by rapid change and widespread information dissemination, Yusuf al-Qaradawi's works provide guidance for Islamic educators and students to understand and confront contemporary challenges. This abstract outlines his influence in enriching Islamic religious education in the digital era, highlighting his significant contributions in integrating Islamic values with technology, addressing contemporary issues, and fostering critical thinking among Muslim students. By understanding his influence, we can appreciate the role played by Yusuf al-Qaradawi's works in shaping a meaningful and relevant Islamic religious education for the current digital generation